2020
DOI: 10.3390/polym12051182
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Sorption Capacity Examination for a Novel Hydrogel Composite Based on Gellan Gum and Graphene Oxide (GG/GO)

Abstract: A novel hydrogel composite based on gellan gum and graphene oxide (GG/GO) was synthesized, characterized and tested for sorption capacity in this work. The microstructural, thermogravimetric and spectroscopic analysis confirmed the formation of the GG/GO composite. Comparative batch sorption experiments revealed a sorption capacity of the GG/GO composite for Zn (II) ions of approximately 2.3 higher than that of pure GG. The GG/GO composite exhibits a maximum sorption capacity of 272.57 mg/g at a pH of Zn (II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Our data confirmed that the hydrogels did not affect this important parameter. Only three papers focused on different combinations of GG/PEGDA [ 35,67 ] and GG/GO, [ 68 ] but cell viability was evaluated only in GG/PEGDA hydrogels. In line with our data, they have demonstrated that mesenchymal stromal cells embedded in GG/PEGDA showed a high percentage (above 87%) of viable cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our data confirmed that the hydrogels did not affect this important parameter. Only three papers focused on different combinations of GG/PEGDA [ 35,67 ] and GG/GO, [ 68 ] but cell viability was evaluated only in GG/PEGDA hydrogels. In line with our data, they have demonstrated that mesenchymal stromal cells embedded in GG/PEGDA showed a high percentage (above 87%) of viable cells.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of pH from 1 up to 7 led to the improvement of their sorption capacity due to the decrease of the protonation degree of the amine groups, and thus the number of binding sites available for the sorption of Copper(II) and Nickel(II) ions increased significantly. The carboxylate groups of the GG 1 and GG 3 microparticles are non‐ionized at pH values less than 3.4 and become ionized at pH values higher than 4.4 [40] . Thus, with increasing of the pH values, the carboxylate groups belonging to the grafted GLL cause the swelling of GG 1 and GG 3 microparticles, leading to the expansion of the polymer chain facilitating the penetration of metal ions to the binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…Developing countries like Malaysia have been exposed to heavy metal pollution that comes from different sources, like agriculture, industrial and domestic activities, which predominantly contribute to a high concentration of heavy metal ions discharge through sewage and straight into water source [ 1 , 2 , 3 ]. Accumulation of these hazardous inorganic pollutants could eventually enter the food chains and cause a detrimental effect on living organisms and human health with high toxicity and carcinogenicity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the sorbent can be derived from a low-cost material, such as agricultural waste, natural material, modified biopolymer and industrial by-product [ 9 , 10 ]. As a result, there are rising numbers of studies on the sorption of heavy metal by polysaccharides-based hydrogel owing to their accessibility, economical, renewability, biodegradability and environmental compatibility to practice green chemistry [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation